Azimuthal single- and double-spin asymmetries in semi-inclusive deep-inelastic lepton scattering by transversely polarized protons - Airapetian, A.; Akopov, N.; Akopov, Z.; Aschenauer, E. C.; Augustyniak, W.; Avakian, R.; Bacchetta, A.; Belostotski, S.; Bryzgalov; Capitani, G. P.; Cisbani, E.; Ciullo, G.; et al. (Journal of High Energy Physics, 2020)
A comprehensive set of azimuthal single-spin and double-spin asymmetries in semi-inclusive leptoproduction of pions, charged kaons, protons, and antiprotons from transversely polarized protons is presented. These asymmetries include the previously published HERMES results on Collins and Sivers asymmetries, the analysis of which has been extended to include protons and antiprotons and also to an extraction in a three-dimensional kinematic binning and enlarged phase space. They are complemented by corresponding results for the remaining four single-spin and four double-spin asymmetries allowed in the one-photon-exchange approximation of the semi-inclusive deep-inelastic scattering process for target-polarization orientation perpendicular to the direction of the incoming lepton beam. Among those results, significant non-vanishing cos (phi-phi(S)) modulations provide evidence for a sizable worm-gear (II) distribution, g(1T)(q) (x, p(T)(2)). Most of the other modulations are found to be consistent with zero with the notable exception of large sin (phi(S)) modulations for charged pions and K+.
CRIS-Team WoS Importer:2021-01-22

Beam-helicity asymmetries for single-hadron production in semi-inclusive deep-inelastic scattering from unpolarized hydrogen and deuterium targets - Airapetian, A.; Akopov, N.; Akopov, Z.; Aschenauer, E. C.; Augustyniak, W.; Belostotski, S.; Blok, H. P.; Bryzgalov, V.; Capitani, G. P.; Cisbani, E.; Ciullo, G.; Contalbrigo, M.; et al. (Physics Letters B, 2019)
A measurement of beam-helicity asymmetries for single-hadron production in deep-inelastic scattering is presented. Data from the scattering of 27.6 GeV electrons and positrons off gaseous hydrogen and deuterium targets were collected by the HERMES experiment. The asymmetries are presented separately as a function of the Bjorken scaling variable, the hadron transverse momentum, and the fractional energy for charged pions and kaons as well as for protons and anti-protons. These asymmetries are also presented as a function of the three aforementioned kinematic variables simultaneously.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Beam-helicity asymmetries; Deep-inelastic scattering; Nucleon structure; Transverse-momentum dependence; Twist-3

Longitudinal double-spin asymmetries in semi-inclusive deep-inelastic scattering of electrons and positrons by protons and deuterons - Airapetian, A.; Akopov, N.; Akopov, Z.; Aschenauer, E. C.; Augustyniak, W.; Avakian, R.; Avetissian, A.; Belostotski, S.; Blok, H. P.; Borissov, A.; Bryzgalov, V.; Capitani, G. P.; et al. (Physical Review D, 2019)
A comprehensive collection of results on longitudinal double-spin asymmetries is presented for charged pions and kaons produced in semi-inclusive deep-inelastic scattering of electrons and positrons on the proton and deuteron, based on the full HERMES data set. The dependence of the asymmetries on hadron transverse momentum and azimuthal angle extends the sensitivity to the flavor structure of the nucleon beyond the distribution functions accessible in the collinear framework. No strong dependence on those variables is observed. In addition, the hadron charge-difference asymmetry is presented, which under certain model assumptions provides access to the helicity distributions of valence quarks.
CRIS-Team WoS Importer:2019-06-21